Wardlaw's perspectives in nutrition - Byrd-Bredbenner, Carol; Berning, Jacqueline R.; Kelley, Danita S.; Abbot, Jackie (New York, NY : McGraw Hill LLC, 2022)
"Wardlaw's Perspectives in Nutrition has the richly-deserved reputation of providing an accurate, current, in-depth, and thoughtful introduction to the dynamic field of nutrition, and the eleventh edition has been enhanced for both students and instructors. This edition continues the tradition of presenting scientific content that is reliable, accurate, and up-to-date, and it incorporates coverage of recent nutrition research, as well as the recent updates to consumer guidelines and tools -- Dietary Guidelines for Americans, MyPlate, Healthy People 2020, and the new Nutrition Facts panel. Timely and intriguing examples, illustrative analogies, clinical insights, culinary perspectives, historical notes, future perspectives, and thought-provoking photos make the text enjoyable and interesting to students and instructors alike"--
Part 1 Nutrition Fundamentals -- Chapter 1: The Science of Nutrition -- Chapter 2: Tools of a Healthy Diet -- Chapter 3: The Food Supply -- Chapter 4: Human Digestion and Absorption -- Part 2 Energy-Yielding Nutrients and Alcohol -- Chapter 5: Carbohydrates -- Chapter 6: Lipids -- Chapter 7: Protein -- Chapter 8: Alcohol -- Part 3 Metabolism and Energy Balance -- Chapter 9: Energy Metabolism -- Chapter 10: Energy Balance, Weight Control, and Eating Disorders -- Chapter 11: Nutrition, Exercise, and Sports -- Part 4 Vitamins and Minerals -- Chapter 12: The Fat-Soluble Vitamins -- Chapter 13: The Water-Soluble Vitamins -- Chapter 14: Water and Major Minerals -- Chapter 15: Trace Minerals -- Part 5 Nutrition Applications in the Life Cycle -- Chapter 16: Nutritional Aspects of Pregnancy and Breastfeeding -- Chapter 17: Nutrition during the Growing Years -- Chapter 18: Nutrition during the Adult Years
Includes bibliographical references and index.
Keywords: Nutrition